The Effect of an IoT-Based DC Power Measurement Instrument Utilizing Arduino NodeMCU on the Outcomes of Basic Physics Laboratory Practicum - Linda Sekar utami; Zulkarnain Zulkarnain; Nurul Akma; Sevinatul Nazati; Iswandi Iswahyudi (Universitas Hamzanwadi, 2025)
In Basic Physics instruction, particularly in laboratory experiments involving direct current (DC) circuits, the need for accurate, real-time, and efficient power measurement tools is critical. Traditional instruments often fall short in delivering such performance, leading to errors and delays in data analysis. To address this issue, this study developed and implemented an Internet of Things (IoT)-based power measurement tool utilizing Arduino NodeMCU, capable of real-time data transmission and processing through Wi-Fi connectivity. The integration of current and voltage sensors enables more accurate and accessible DC power measurements for educational purposes.This research employed a quantitative approach using a one-group pretest-posttest quasi-experimental design. A total of 12 students enrolled in the Basic Physics Laboratory course participated in the study. The effectiveness of the tool was evaluated through pretest and posttest assessments, student response questionnaires, and observational data. Normality testing (Shapiro-Wilk) showed that both pretest (p = 0.262) and posttest (p = 0.284) scores were normally distributed. A paired sample t-test revealed a significant improvement in students’ conceptual understanding (t = -8.20, p = 5.14 × 10⁻⁶). The average normalized gain (N-Gain) score was 0.565, indicating a medium level of improvement, with 75% of students falling in the medium category and 25% in the high category. Student feedback also reflected a positive perception of the tool, with an average response score of 84.5 out of 100. These results suggest that the IoT-based measurement tool not only enhances the accuracy and efficiency of data collection in Basic Physics experiments but also improves students’ conceptual understanding and engagement. The innovation aligns with modern educational goals by integrating digital technology into science instruction, preparing students for real-world scientific and technological challenges.